INCREASE IN NUTRITION AND BIOLOGICAL VALUE OF WHITE BREAD WITH USE OF THE GRAIN MIX «OMEGA-6» - Kizatova Maigul Zhalelovna,; Pronina Yuliya Gennad’evna,; Nabieva Zhanar Serikbolova,; Nurgozhin Zhuldyz Kanatovna,; Gumarov Bahtiyar, (Scientific Journal of Pedagogy and Economics, 2019)
In the course of research work, scientists of the Almaty Technological University have developed a technology for the production of bread on the basis of the Omega-6 grain mixture. The composition of the grain mixture includes grains and oilseeds: germinated corn, amaranth, flax seeds, sunflower seeds, pumpkins, sesame, wheat bran. This article presents the results of studies of the nutritional and biological value of wheat bread made from flour of the 1st grade and wheat bread with the addition of the "Omega-6" grain mixture. When developing the formulation of grain mixtures based on grains and oilseeds, special attention was paid to the selection of enriching components of plant origin, depending on their functional orientation. In order to determine the optimal composition of the grain mixture, various versions of the ratios of the components were made and pastries were made using them. First of all, we focused on organoleptic characteristics, such as appearance, taste, aroma, color and porosity. According to the results of the analysis of the organoleptic indicators of variants of grain bread, using different dosages of the components of the Omega-6 grain mixture, clearly demonstrated using a profilogram, their optimal ratio was revealed. The optimum ratio: corn - 63%, amaranth - 1%, sunflower seeds - 2%, pumpkin seeds - 2%, flax seeds - 15%, sesame seeds - 2%, wheat bran - 15%. Additionally, baking was carried out to determine the optimal dose of introducing the "Omega-6" grain mixture into the recipe from 5 to 30%. The best result in organoleptic and physico-chemical properties, the sample was obtained by adding 20% grain mixture. The finished products were sent to determine the nutritional and biological value of bread on the basis of the grain mixture "Omega-6" to the accredited testing laboratory "Food Safety". The following indicators of the control and experimental samples were determined: mass fraction of protein, fat, carbohydrates, vitamins of group B and vitamin E, magnesium, amino acid composition and antioxidant activity, microbiological indicators using modern standard research methods. According to the results of the analysis, it was found that the content of essential amino acids increased by about 56.6%. The magnesium content increased by 33.8%. Sodium content increased by 7.3%. Potassium levels increased by 10.2%. Antioxidant activity in grain bread increased by 1.89 times compared with the control. The use of the "Omega-6" grain mixture in bread products allowed to increase the content of group B vitamins, vitamin E. The amount of mesophilic aerobic and optional anaerobic microorganisms decreased by 50% in experimental bread. Shelf life 72 hours. Thus, the use of the "Omega-6" grain mixture in the bakery industry will expand the range of grain types of bread with increased nutritional and biological value.